Global burden of colorectal cancer in 2020 and 2040: incidence and mortality estimates from GLOBOCAN. Issue 2 (8th September 2022) - Morgan, Eileen; Arnold, Melina; Gini, A; Lorenzoni, V; Cabasag, C J; Laversanne, Mathieu; Vignat, Jerome; Ferlay, Jacques; Murphy, Neil; Bray, Freddie
Abstract : Objective: Colorectal cancer (CRC) is the third most common cancer worldwide. The geographical and temporal burden of this cancer provides insights into risk factor prevalence and progress in cancer control strategies. We examine the current and future burden of CRC in 185 countries in 2020 and 2040. Methods: Data on CRC cases and deaths were extracted from the GLOBOCAN database for the year 2020. Age-standardised incidence and mortality rates were calculated by sex, country, world region and Human Development Index (HDI) for 185 countries. Age-specific rates were also estimated. The predicted number of cases and deaths in 2040 were calculated based on global demographic projections by HDI. Results: Over 1.9 million new CRC cases and 930 000 deaths were estimated in 2020. Incidence rates were highest in Australia/ New Zealand and European regions (40.6 per 100 000, males) and lowest in several African regions and Southern Asia (4.4 per 100 000, females). Similar patterns were observed for mortality rates, with the highest observed in Eastern Europe (20.2 per 100 000, males) and the lowest in Southern Asia (2.5 per 100 000, females). The burden of CRC is projected to increase to 3.2 million new cases and 1.6 million deaths by 2040 with most cases predicted to occur in high or very high HDI countries. Conclusions: CRC is a highly frequent cancer worldwide, and largely preventable through changes in modifiable risk factors, alongside the detection and removal of precancerous lesions. With increasing rates in transitioning countries and younger adults, there is a pressing need to better understand and act on findings to avert future cases and deaths from the disease.